(untitled) (Global Journal of Human-Social Science, 2016)
One objective of Healthy People 2020 identifies the use of information technology (IT) as a health communication strategy for the promotion of population health and health equity. The purpose of this assignment is to describe creative application of evidence-based best practices through userfriendly web designs. It is integral for all educators, especially health professionals, to use relevant I T,as delivery of health information and services continues to expand. Using eportfolios in classroom assignments and as a capstone activity can assist faculty members with evaluating and understanding student outcomes. E-portfolio and technology are not foreign concepts to students, but student understanding of what it means to be a professional, and to integrate professional concepts into personal and professional behaviors, were necessary at the onset of educational programs. Using e-portfolios promoted critical reflection; particularly when students were introduced early in their professional programs to the collection of relevant artifacts.